2018
DOI: 10.1056/nejmsa1706808
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Cost Sharing for Screening Mammography in Medicare Advantage Plans

Abstract: BACKGROUND The Affordable Care Act (ACA) required most insurers and the Medicare program to eliminate cost sharing for screening mammography. METHODS We conducted a difference-in-differences study of biennial screening mammography among 15,085 women 65 to 74 years of age in 24 Medicare Advantage plans that eliminated cost sharing to provide full coverage for screening mammography, as compared with 52,035 women in 48 matched control plans that had and maintained full coverage. RESULTS In plans that eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Our study among others demonstrate that ACA cost share elimination did not result in increased screening rates unlike much earlier efforts to reduce financial barriers to preventive services, likely due to the high proportion of employerinsured women who already had screening cost share eliminated prior to the ACA implementation. Our results are consistent with Trivedi et al who reported no increase in screening adherence in plans already had full coverage for screening mammography during the study duration 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study among others demonstrate that ACA cost share elimination did not result in increased screening rates unlike much earlier efforts to reduce financial barriers to preventive services, likely due to the high proportion of employerinsured women who already had screening cost share eliminated prior to the ACA implementation. Our results are consistent with Trivedi et al who reported no increase in screening adherence in plans already had full coverage for screening mammography during the study duration 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of the impact of the ACA no cost policy on colorectal cancer screening and mammography have found positive effects among the Medicare population (Hamman and Kapinos, 2015; Sabatino et al, 2016; Wan et al, 2015; Jena et al, 2017; Trivedi et al, 2018), but mixed or null results among the commercially insured (Fedewa et al, 2015; Richman et al, 2015; Han et al, 2015; Mehta et al, 2015). The single previous study that included cervical cancer screenings is consistent with our finding of no result (Han et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Despite changes to health care policy that provide more expansive access to insurance, women of color continue to experience inequitable health outcomes. For example, health care reform through the ACA played a pivotal role in reducing financial impediments to accessing mammography (Fazeli Dehkordy et al., 2019; Trivedi et al., 2018); yet, barriers to mammography persist. Despite interventions such as mobile mammography vans that bring physical access to communities (Stanley et al., 2017), Black women continue to lag behind in mammography screening.…”
Section: Discussionmentioning
confidence: 99%